Importance of and Approach to Taking a History of Exposures to Occupational Respiratory Hazards - Weissman, David N.; Radonovich, Lewis J. (Seminars in Respiratory and Critical Care Medicine, 2023)
Occupational respiratory diseases are caused by exposure to respiratory hazards at work. It is important to document those exposures and whether they are causing or exacerbating disease because these determinations can have important impacts on diagnosis, treatment, job restrictions, and eligibility for benefits. Without investigation, it is easy to miss clinically relevant exposures, especially in those with chronic diseases that can have work and nonwork causes. The first and most important step in identifying exposures to respiratory hazards at work is to take an appropriate history. For efficiency, this is a two-step process. An initial quick screening history is done by asking only a few questions. Follow-up questions are asked if there are positive responses to the screening questions or if an occupational etiology is suspected based on the clinical presentation. Electronic health records have promise for facilitating this process. Follow-up to the screening history may include additional questions, evaluating additional sources of information about workplace exposures, and medical testing. Radiographic findings or tests conducted on noninvasive samples or lung tissue can be used as biomarkers. Online resources can be used to learn more about exposures associated with occupations and industries and to see if investigations evaluating exposures were performed in the patient's own workplace. It is important to adhere to the patient's wishes about contacting the employer. With patient consent, the employer can be an important source of information about exposures and, if a problem exists, has an important role in taking corrective action. Consultation for challenging cases is available from a variety of professional and governmental entities. If a clinician identifies a significant public health issue, such as an occupational disease outbreak, it is important to notify relevant public health authorities so that steps can be taken to prevent additional exposures and appropriately care for those already exposed.
Keywords: respiratory disease; occupational; hazardous exposure; medical history; exposure assessment